(untitled) (Medico Legal Update, 2021)
Background: This study is concerned with determining the severity of preeclampsia according to the value of serum albumin .Materials and Method : 100 women were divided into 4 groups according to their blood pressure [control (n=22), gestational hypertension (n=25), mild preeclampsia (n=29), severe preeclampsia (n=24)].Concerning about comparison of serum albumin level for each woman . Also the following informations were taken in consideration: age, gestational age, parity, systolic blood pressure and diastolic blood pressure .Results : comparing serum albumin level between the groups shows a significant difference (p?0.05). Analysis of data shows a significant difference in age between control and severe preeclampsia (p=0.04) . The difference in gestational age was significant between control and other groups (p?0.05) and a statistically significant difference in systolic and diastolic blood pressure between the groups (p?0.05). Conclusion: This study showed that serum albumin level is lower in mild and severe preeclampsia in comparison with normal and hypertensive cases.